2014
DOI: 10.1038/nm.3740
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the PRKCD–FBXO25–HAX-1 axis attenuates the apoptotic response and drives lymphomagenesis

Abstract: We searched for genetic alterations in human B cell lymphoma that affect the ubiquitin-proteasome system. This approach identified FBXO25 within a minimal common region of frequent deletion in mantle cell lymphoma (MCL). FBXO25 encodes an orphan F-box protein that determines the substrate specificity of the SCF (SKP1-CUL1-F-box)(FBXO25) ubiquitin ligase complex. An unbiased screen uncovered the prosurvival protein HCLS1-associated protein X-1 (HAX-1) as the bona fide substrate of FBXO25 that is targeted after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 51 publications
0
55
0
Order By: Relevance
“…These findings, coupled with our recent observations, indicating that HAX-1 can suppress ER stress-induced apoptosis (14), reveal a previously unidentified paradigm of cell death regulation by HAX-1 in two different cellular organelles. Growing evidence demonstrates an axiomatic prosurvival role of HAX-1, and human mutations of this protein have been shown to associate with diseases characterized of altered cell viability, such as congenital neutropenia (15), neurodevelopmental retardation (26), and mantle cell lymphoma (11). Although HAX-1 has been known to predominantly localize to mitochondria in various tissues and cell types (8), and mitochondria are known for their gate-keeping role in cell death activation, it is surprising that there are only a few studies addressing the function of HAX-1 in regulation of cell death by this organelle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings, coupled with our recent observations, indicating that HAX-1 can suppress ER stress-induced apoptosis (14), reveal a previously unidentified paradigm of cell death regulation by HAX-1 in two different cellular organelles. Growing evidence demonstrates an axiomatic prosurvival role of HAX-1, and human mutations of this protein have been shown to associate with diseases characterized of altered cell viability, such as congenital neutropenia (15), neurodevelopmental retardation (26), and mantle cell lymphoma (11). Although HAX-1 has been known to predominantly localize to mitochondria in various tissues and cell types (8), and mitochondria are known for their gate-keeping role in cell death activation, it is surprising that there are only a few studies addressing the function of HAX-1 in regulation of cell death by this organelle.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, global ablation of HAX-1 was shown to result in death by 14 wk of age due to neuronal degeneration from excessive cell death (10). In addition, a recent study demonstrated that degradation of HAX-1 triggers cell death in human B-cell lymphoma, further supporting the pivotal role of HAX-1 in dictating cell survival (11). Although HAX-1 has been studied in various cell types since its discovery in 1997 (7), its presence in cardiomyocytes was only recently identified.…”
mentioning
confidence: 95%
“…Cell samples were lysed in lysis buffer (NaCl 150 mM, Tris-HCl 50 mM, MgCl 2 5 mM, EDTA 1 mM, 0.1% NP-40, 5% glycerol and protease inhibitors), unless otherwise specified. Extract preparation, immunoprecipitation and immunoblotting have been previously described [49][50][51] . For immunoprecipitations (IPs), cell lysates were incubated with Flag-M2 agarose beads (Sigma) for Flag-specific IPs, HA-7 agarose beads (Sigma) for HA-specific IPs or protein A-sepharose beads (GE Healthcare), together with primary rabbit antibodies, for binding of endogenous proteins.…”
Section: Competing Financial Interestsmentioning
confidence: 99%
“…They interface with a large array of proteins, attesting to a complex biological role. Hax-1 has recently been shown to be a substrate for ubiquitin-mediated degradation by SCF(Fbxo25) (134). Interestingly, Hax-1 and Fbxo25 normally reside in distinct subcellular compartments, Hax-1 at the mitochondria, and Fbxo25 in the nucleus, but upon stimulation with etoposide, protein kinase C δ phosphorylates both proteins triggering (135).…”
Section: Resisting Cell Deathmentioning
confidence: 99%